METHODOLOGICAL ASPECTS OF USING THE GOOGLE TRANSLATE APPLICATION TO FOREIGN LANGUAGE LESSONS - VEVERIȚA, Tatiana (Acta et Commentationes, Sciences of Education, 2019)
This article analyzes the role of Google Translate in studying foreign languages. The main ideas of the article relate the importance of information technologies in the development of foreign language learning skills and how these can become pedagogical tools that help to increase the level of understanding of a foreign language